Diagnostic Utility of Lymphoid Enhancer Binding Factor 1 Immunohistochemistry in Small B-Cell Lymphomas. Issue 3 (7th March 2017) - Menter, Thomas; Trivedi, Pritesh; Ahmad, Raida; Flora, Rashpal; Dirnhofer, Stephan; Tzankov, Alexandar; Naresh, Kikkeri N.
Abstract: Objectives: Recent studies have shown that lymphoid enhancer binding factor 1 (LEF1) is a useful marker for chronic lymphocytic B-cell leukemia (CLL)/small lymphocytic lymphoma. Yet, it is not still being widely used in a diagnostic setting. In this study, we document the experience with LEF1 immunohistochemistry during routine diagnostics. Methods: In total, 191 B-cell lymphoma cases from Hammersmith Hospital, Imperial College NHS Healthcare Trust (London, UK) were investigated by immunohistochemistry for LEF1 during routine diagnostic workup. These cases included both bone marrow trephines and lymph node biopsy specimens. The monoclonal antibody clone EPR2029Y was used. Results: LEF1 expression was strong and diffuse (>70% of cells) in most cases. Few CLL cases showed a staining in proliferation centers only. Seventy-seven of 80 CLL cases expressed LEF1. Other entities expressing LEF1 included one of 38 follicular lymphomas, two of 33 marginal zone lymphomas, and one diffuse large B-cell lymphoma with a background of follicular lymphoma grade 3B. Sensitivity for LEF1 for the diagnosis of CLL was 0.96, and specificity was 0.93. Conclusions: In this study, we could demonstrate the diagnostic utility of LEF1. LEF1 is a sensitive and specific marker for CLL and is helpful in the diagnosis of diagnostically challenging small B-cell lymphomas.